To solve the quadratic equation \(46x^2 - 138x = 0\) by factoring out the greatest common factor (GCF), we first find the GCF of the two terms.
-
The GCF of \(46x^2\) and \(138x\) is \(46x\).
-
Factoring out \(46x\) from the equation: \[ 46x(x - 3) = 0 \]
-
Now, we set each factor equal to zero:
- First factor: \[ 46x = 0 \implies x = 0 \]
- Second factor: \[ x - 3 = 0 \implies x = 3 \]
Thus, the solutions to the equation \(46x^2 - 138x = 0\) are:
- \(x = 0\)
- \(x = 3\)
So the correct response is: The solutions are x=0 and x=3.